Job Satisfaction and Associated Factors among Anesthetists Working in Amhara National Regional State, Northwest Ethiopia, May 2017: A Multicenter Cross-Sectional Study - Demeke Yilkal Fentie; Henos Enyew Ashagrie; Habtamu Getinet Kasahun (Anesthesiology Research and Practice)
Background. Job satisfaction is an important determinant of health staff’s motivation, retention, and performance. Difficulties in critical decision-making and problems with lack of respect and recognition lead to lower job satisfaction level among anesthetists. It leads to high turnover intention, dropout from the profession, burnout, impaired health status of anesthetists, and lower work performance. Objective. The aim of this multicenter cross-sectional study was to assess the level of job satisfaction and associated factors among anesthetists working in Amhara National Regional State. Methods. A multicenter cross-sectional study was conducted from April 1 to June 30, 2017. Ninety-eight anesthetists that were working in Amhara National Regional State Hospitals were involved in this study. The structured questionnaire was scored on five-point Likert scales. Data were analyzed using Statistical Package for Social Sciences version 20. Binary logistic regression was used to measure statistical significance between dependent and each independent variable. Variables with P value of ≤0.2 on crude analysis were taken into multivariate analysis, and P value 0.05 and 95% CI was used as cut off point. Result. 98 out of 104 participants were involved in this study with a response rate of 94.3%. The overall level of job satisfaction was 46.9%. Anesthetists in academic working position were satisfied with the odds of about 2.3 (AOR = 2.269; CI = 1.137–6.740) compared to those in clinical working position. Anesthetists were least satisfied with coworker relationships (37.8%), work schedule (43.9%), professional opportunity (46.9%), and recognition (49%) while they were most satisfied from their control of responsibility (59.2%), social interaction (55%), and salary and benefits (51%). Conclusion and Recommendation. Job satisfaction of anesthetists was low, and we suggest that facilitation of professional development, creation of smooth relationship in working environment, increasing the number of anesthetists, and recognition of the anesthesia professional are of paramount importance to increase job satisfaction of anesthetists.